Culture and sensitivity analysis in rhinitis atrophic: case series - Tjahyadewi, Shelly; Aditomo, Rano; Rahayu, Rahayu; Sulistyanto, Agung; Pasaribu, Nurfauziati (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2024)
Atrophic rhinitis is a rare condition affecting the nasal mucosa, characterized by progressive nasal congestion, foul odor, and thick nasal secretions. It is classified into two types: primary (idiopathic), where the cause remains unknown, and secondary, which develops due to another underlying condition. Primary atrophic rhinitis, often called ozaena (from the Greek word for "stench"), has also been described as acute necrotizing rhinitis, catarrhal atrophic rhinitis, or coryza foetida. This condition predominantly affects women, with a reported ratio of 6:1.5. It is more prevalent in tropical regions and among populations with low socioeconomic status and poor hygiene, although its exact etiology remains unclear. Diagnosis is primarily clinical, based on a triad of symptoms: fetor, greenish nasal crusts, and an abnormally wide nasal cavity, often observed in advanced cases. This case series presents two rare instances of atrophic rhinitis, highlighting distinct characteristics and risk factors while contributing valuable insights into understanding this uncommon disorder.